EKSPERIMEN PENENTUAN CEPAT RAMBAT BUNYI DI UDARA DENGAN ALAT PRAKTIKUM PADA DUA UKURAN PIPA - Kristina Kristina Neftalia Sihombing; Tika Yuli Yanti; Jeliana Veronika Sirait (JURNAL FIRNAS, 2026)
Abstract: The design of this sound resonance lab tool was made to compare the speed of sound propagation in the air in two types of pipes, namely small and large diameter pipes. The working principle of the tool is based on the resonance phenomenon that appears when the pipe is dipped in water, then the length of the air column that produces harmonic tones is sought using a frequency generator application at 1250, 1500, and 1750 Hz. The simple and easy-to-use tool design helps expedite the experimental process. From the results of the experiment on a small pipe, for frequencies of 1250, 1500, and 1750 Hz, the length of the air column was obtained as 13.603 cm, 11.33 cm, and 9.73 cm, respectively, with sound speeds of around 340, 340, and 340.5 m/s. In the large pipe, the results were almost the same: air column lengths of 13.6 cm, 11.34 cm, and 9.73 cm with sound speeds of 340, 340, and 340.5 m/s, respectively. From all these measurements, it can be concluded that there is no significant difference between the small and large pipes. The pattern of the relationship between frequency and air column length also remains the same, namely, the higher the frequency, the shorter the length of the resonating air column. Meanwhile, the speed of sound in air remains in a constant range, namely between 340 and 340.5 m/s.